2021
DOI: 10.1002/trtr.1966
|View full text |Cite
|
Sign up to set email alerts
|

(Info)Graphically Inclined: A framework of infographic learning

Abstract: Infographics are appearing in children’s magazines, picture books, and informational texts. Understanding, and ultimately creating, these complex visual representations of information or data requires higher level thinking skills to analyze and understand how the text and graphics work together to convey meaning. The authors provide a framework for infographic exploration, investigation, creation, and integration into larger writing pieces. Each phase of the framework includes specific considerations to assist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…Alternative measurement tools and systems are needed for online environments (Albayrak, 2022). For this reason the research has shown that designing or using infographics is effective in students' learning processes (Tsai et al, 2020;Smith & Robertson, 2021;Çaka & Dursun, 2022). An experimental study concluded that the group that used infographics in the teaching process had better motivation and could learn new subjects faster (Bicen & Beheshti, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Alternative measurement tools and systems are needed for online environments (Albayrak, 2022). For this reason the research has shown that designing or using infographics is effective in students' learning processes (Tsai et al, 2020;Smith & Robertson, 2021;Çaka & Dursun, 2022). An experimental study concluded that the group that used infographics in the teaching process had better motivation and could learn new subjects faster (Bicen & Beheshti, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Somehow, this is in accordance with the results of Hassan's research. (2016: 95), which shows that static infographics and videos are properly designed and used in a more effective process (Smith & Robertson, 2021;Wulandari, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Even if there is beauty in design elements, their appearance is not dominant. Instead, it prioritizes simplicity in its appearance [24].…”
Section: ) Geographic Information Basedmentioning
confidence: 99%